THE STRATEGY FOR HEALTH DEVELOPMENT AND NATIONAL RESILIENCE IN THE PERSPECTIVE OF THE NATION'S POWER - Lardo, Soroy (Jurnal Pertahanan dan Bela Negara, 2020)
The nation’s resilience means the concept and power of maintaining national resilience which includes existence in the midst of civilization and strategic environmental changes, towards the dynamic conditions of national resilience to maintain order, stability, and the potential for change (the stability idea of changes). The challenges and problems of national resilience are dynamic variants that require a comprehensive way of thinking on the systems, policies, and strategies of nationality behavior (behavior science) supported by patriotism and the energy security of the nation's health towards the role of the Indonesian National Armed Forces (TNI) to fill the zone and the accumulation of health development that illustrates the performance of self-reliance and national resilience. The nation's health power in the perspective of structural and participatory strength starts with the ability to drive leadership, metabolic health community and agent of change that meets the reliability value of High- Reliability Organization (HRO). The reliability that is formed will trigger the spirit of innovation and out the box to assemble a network for change so that it is manifested as a performance of professional reliability that upholds the nation's health potential and national resilience. The synergy of the National Health System (SKN) and the Defense Health System (Siskeshan) are interrelated networks to support efforts to empower the strategic value of national health. This strategy strengthens national resilience (one health) network towards the complexity of global health threats that threaten national resilience. The global challenge with the emergence of a Public Health Emergency in the form of an outbreak that is so rapid with unpredictable problems triggers every country to strengthen the nation's power to synergize health development based on the national resilience system. Keywords: The National Resillience, Leadership, Agent of Change, Synergy of The National Health System (SKN) and The Defense Health System (Siskeshan), Unhan